The time of money in finance and US society - Elena Esposito (Finance and Society, 2018)
Traditional societies were defined by a prevalence of the past in the definition of the present. United States (US) society seems to show the opposite trend: the present is defined as the preparation of the future. Financial temporality can be seen as an example of the present use of the future, transforming future possibilities into available wealth. As the financial crisis has shown, however, the temporality of the future is more complex and circular. This article deals with quantitative easing (QE) as a financial instrument with an essentially temporal nature (in the sense that it uses time and acts on the future and on expectations). The success of QE in the US economy reveals essential aspects of US temporality, but also raises questions as to how it may differ from European temporality. The analysis of QE measures and their impact also offers ways to assess whether and by which means politics can intervene into finance, as well as what consequences and uncertainties are created in the process.
Keywords: 300; Structured finance; risk; futurity; quantitative easing; performativity; money